Pomen nevrotrofičnih dejavnikov pri nevrodegenerativnih boleznih - Horvat, Selena (Farmacevtski vestnik, 2024)
Proteins exerting neurotrophic activity, so-called neurotrophic factors, promote cell survival, differentiation, regeneration and maintenance of neurons in the central nervous system. Because of their action, they are important in neurodegenerative diseases, as they protect neurons from neuronal damage and promote their regeneration. Mimicking the mode of action of neurotrophic factors and molecules that exert neurotrophic activity thus presents opportunitiesfor the development of new therapeutic approaches for the treatment of neurodegenerative diseases.
Keywords: neurodegeneration; neurodegenerative diseases; neurotrophic factors; neurotrophins; nevrodegeneracija; Nevrodegenerativne bolezni; nevrotrofični dejavniki; nevrotrofini; trofična podpora; trophic support